Enhanced Hydrogen Production over C-Doped CdO Photocatalyst in Na2S/Na2SO3 Solution under Visible Light Irradiation - Quan Gu; Huaqiang Zhuang; Jinlin Long; Xiaohan An; Huan Lin; Huaxiang Lin; Xuxu Wang (International Journal of Photoenergy)
The C-doped CdO photocatalysts were simply prepared by high-temperature solid-state process. The as-prepared photocatalysts were characterized by X-ray powder diffraction (XRD), diffuse reflectance spectroscopy (UV-Vis DRS), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The results demonstrated that the carbon was doped into CdO, resulting in the red-shift of the optical absorption of CdO. The photocatalytic behavior of CdO and C-doped CdO was evaluated under the visible light irradiation by using the photocatalytic hydrogen evolution as a model reaction. The C-doped CdO photocatalysts had higher photocatalytic activity over parent CdO under visible light irradiation. The results indicated that the H2 production was due to the existence of CdS and the enhancement of visible light photocatalytic activity of H2 production was originated from the doping of carbon into the CdO lattice. The probably reaction mechanism was also discussed and proposed.